2012
DOI: 10.4018/jgim.2012070102
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study of Determinants of E-Commerce Adoption in SMEs in Vietnam

Abstract: Experts and business pundits forecasted drastic changes in Vietnam’s fledgling e-commerce when the Southeast Asian country became an official member of the World Trade Organization (WTO) in 2007. Over the past few years, as part of the Reform – called Doi moi – some Vietnamese enterprises have adopted e-commerce and already benefitted from it. In this research, the authors adapt the Technology-Organization-Environment (TOE) framework and test a model of e-commerce adoption including numerous internal and exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
63
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(76 citation statements)
references
References 61 publications
10
63
2
1
Order By: Relevance
“…In respect to the latter two conclusions, the acceptance of web 2.0 technologies by potential customers is in rapid expansion, thanks to the standardisation, low prices and ubiquity of the modern technologies. In addition to this literature, some recent publications have researched the adoption of specific online tools and applications by SMEs (Low & Johnston, 2009;Palmer et al, 2012;Van Huy et al, 2012). Generally, the positive consequences of the technological adoption are recognised, but the overall positioning of SMEs is not discussed.…”
Section: Summary On Sme's Technology Adoptionmentioning
confidence: 99%
“…In respect to the latter two conclusions, the acceptance of web 2.0 technologies by potential customers is in rapid expansion, thanks to the standardisation, low prices and ubiquity of the modern technologies. In addition to this literature, some recent publications have researched the adoption of specific online tools and applications by SMEs (Low & Johnston, 2009;Palmer et al, 2012;Van Huy et al, 2012). Generally, the positive consequences of the technological adoption are recognised, but the overall positioning of SMEs is not discussed.…”
Section: Summary On Sme's Technology Adoptionmentioning
confidence: 99%
“…Social factors are concerned with informal regulations and are also implicated in the adoption of E-Commerce (Lin et al, 2011). For example, websites in Vietnam are perceived as being 'merely places for promotion; not for purchase' because 'Vietnamese consumers are used to the practice of seeing and touching before buying' (Van Huy et al, 2012).One of the social factors to affect E-Commerce is language of online content. Mansell (2001) and Gattiker et al,.…”
Section: Perceived Environmental Ereadinessmentioning
confidence: 99%
“…Roztocki and Weistroffer (2008b) state that ICT in transition economies has been used as a support tool of basic business functions such as reporting and calculating rather than as an innovation enabler. Furthermore, Van Huy et al (2012) found that adoption of e-commerce in small and medium-sized firms in another transition economy, namely Vietnam, depends strongly on factors such as employees' knowledge of e-commerce, the resources available to the enterprise, and the size of the enterprise, as well as characteristics of managers and the local business environment. This area offers fertile ground for future research, in which the e-VM maturity model may serve as a useful tool.…”
Section: Implications Of the Case Analyses And Suggestions For Furthementioning
confidence: 98%